Effectiveness of a mHealth platform-based lifestyle integrated multicomponent exercise (PF-Life) program to reverse pre-frailty in community-dwelling older adults: a randomized controlled trial study protocol - Li, Na; Huang, Feng; Wang, Nan; Lin, Siyang; Yuan, Yin; Zhu, Pengli (Frontiers in Public Health, 2024)
Background Pre-frailty represents an ideal window of opportunity to potentially prevent frailty and disability. Early and effective interventions to delay or reverse pre-frailty are public health imperative. The present trial aims to evaluate the effectiveness and underlying mechanisms of mobile health (mHealth) platform-supported lifestyle-integrated multicomponent exercise (PF-Life) to reverse pre-frailty in community-dwelling older adults. Methods This is an open-label, prospective, two-arm parallel randomized controlled trial with allocation concealment and outcome assessment blinding. We aim to recruit 140 pre-frail community-dwelling older adults who will be randomized into two groups. The control group will receive a health education program, while the intervention group will receive PF-Life training as planned for 1 year. The proportion of pre-frailty, functional performance (muscular strength, aerobic capacity, flexibility, and balance), body composition, and physical activity will be measured at pre-intervention, post-intervention, and 12-month follow-up. Inflammatory biomarkers will also be collected to explore the underlying mechanisms. Discussion This is the first study to evaluate the effects of a novel digital lifestyle-integrated multicomponent exercise for pre-frail older people. The results of this trial will provide much-needed information on the short-and long-term effects of PF-Life based on functional performance and body composition. Meanwhile, inflammatory biomarkers and physical activity levels will be used to elucidate the underlying mechanisms of PF-Life. The findings from this trial will provide evidence for the effectiveness of lifestyle multicomponent exercise intervention supported by the mHealth platform that may reverse or even halt the onset of frailty. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=176477, identifier ChiCTR2200063431.